How important are different non-native conifers in Britain to Common Crossbills Loxia curvirostra curvirostra?. Issue 1 (2nd January 2019) - McNab, Eilidh; Summers, Ron; Harrison, Gavin; Park, Kirsty J.
ABSTRACT: Capsule: Pines physically defend their seeds against seed-eating birds and mammals more than spruces or larches. Cone characteristics reflect the rate at which Common Crossbills Loxia curvirostra curvirostra extract seeds from different non-native conifers in Britain. Aims: To assess the profitability of different non-native conifers in Britain for Common Crossbills in winter. Methods: We measured cone and seed parameters of conifers (Norway Spruce Picea abies, Sitka Spruce Picea sitchensis, Lodgepole Pine Pinus contorta and Japanese Larch Larix kaempferi ) introduced into Britain and compared these with the native Scots Pine Pinus sylvestris . Feeding trials with captive Common Crossbills assessed intake rates. Results: The pines had thick and long scales, Japanese Larch had thin, short scales but thick seed coats and Sitka Spruce had thin, papery and short scales, and the thinnest seed coat. The two spruce species had more seeds per cone and the kernels had a higher energy content than the pines and larch. Feeding trials, simulating cones in winter, found that Common Crossbills failed to access seeds in closed Scots Pine cones. They also had difficulty in prising the scales of closed Lodgepole Pine cones but were able to forage on partially open cones. They took longer to extract seeds from large, open Lodgepole Pine cones than small ones, reflecting the effect of increasing scale thickness in larger pine cones. They also took longer to extract Lodgepole Pine seeds than Sitka Spruce and larch seeds. Although Common Crossbills could extract seeds quickly from open Sitka Spruce cones, the small seed size made the energy intake rate similar to Japanese Larch, if all seeds contained a kernel. However, after accounting for the proportion of seeds with a kernel, Sitka Spruce was the more profitable. Conclusion: The conifer food resource for crossbills in Britain has changed through the planting of non-native conifers. The physical properties of the cones and seeding phenology influence the rate at which Common Crossbills can extract seeds.